Assessment of mental health status among kalitheerthalkuppam farmers Puducherry: a cross-sectional study - Ponkash, P.; Savitha, G.; Sruthi, E. Shree; Silvester, S. Andrew John (International Journal Of Community Medicine And Public Health, 2025)
Background: Every year, more than 450 million people develop a mental disorder globally. About 75% of people affected by mental disorders live in low-income and middle-income countries (LMICS), and most have no access to appropriate treatment. This study intends to examine how occupational characteristics like time of work, working hours per day impact the mental health of farmers. The aim is to gather data that illuminates the relationship between mental health and occupational characteristic of farmers. Methods: It is a quantitative, cross-sectional study conducted among 152 farmers in a selected village at Puducherry. The validated self-structured questionnaires consisting of sociodemographic profile, anthropometric measurement, occupational characteristics assessing questionnaire and Depression Anxiety and Stress scale-21[DASS-21] were used to collect data. Simple random sampling technique was used for selection of participants. Statistical analysis, IBM SPSS statistics version 25 has been used. Results: In this study we found that, majority were normal weight (n=112, f=73.7%). Mean score of depression M=10, SD=6.12, for anxiety M=10.3, SD=6.32 and stress M=11.40, SD=5.44. Most of the farmers reported heavy workload (n=137, f= 90.1%) and among them (n=85, f =55.92) farmers reported working more than 6 hours a day. There is a significant association between Occupational characteristics and mental health of farmers. Conclusions: Farmers have higher mental health issues. Heavy workload and more working hours per day are independently associated with more mental health problems. Our findings highlight the importance of including mental health within occupational programmes.